Advancements in SnO2-based nanomaterials for efficient dye removal from wastewater - Alok Tiwari; Vishal Sandhwar; Shivendu Saxena; Diksha Saxena; Gourang Damle (Discover Sustainability)
Abstract The dye released from the industries as effluent harms the ecosystem and human beings. The consequences of the dye in the water bodies of the environment have become a matter of great concern for environmentalists and scientists. Dyes that come from different industries should be treated before being released into the environment so that their impact on the environment and living things is reduced. Due to the lack of knowledge on how to remove dye, it is very difficult for any single technique to eliminate this problem. Tin oxide-based nanomaterials have surfaced as a promising material for dye removal, owing to their inherent characteristics, including substantial surface area, robust chemical stability, and inherent photocatalytic activity. This review focuses on analysing the mechanisms underlying dye removal facilitated by tin oxide (SnO2) nanoparticles, encompassing adsorption, photocatalytic degradation, and flocculation processes. This article also explores the diverse range of synthesis methodologies for tin oxide nanomaterials, the applicability of SnO2 in different kinds of synthetic and organic dyes, and the critical need for continued research and development efforts aimed at optimizing tin oxide nanomaterials, ultimately contributing to the realization of more effective and sustainable solutions for addressing the environmental challenges posed by dye pollution in wastewater.